Ancient Greek Philosophia in India as a Way of Life. (27th April 2020) - Moore, Christopher
Abstract: The Greek identification of certain Indian people as philosophoi at the end of the fourth century bce provides unique information about the meaning of the term philosophia, especially with respect to its reference to a certain kind of "way of life" ( bios ), at the time of its greatest maturity (at the start of the Hellenistic period). The Indica of Megasthenes, an ambassador to northern India after the death of Alexander, is our most important evidence; fragments from earlier works by Nearchus and Onesicritus, intellectuals in Alexander's cortege, provide corroboration. This essay argues that late classical Greeks did largely think of philosophia as a way of life.